RECONSTRUCTION NEW PARADIGM FOR MANAGEMENT AND DEVELOPMENT OF ENDOWMENTS - Muhammad Samsuri; Ahmad Khisni; Mahmutarom Mahmutarom; Anis Mahdurohatun (International Journal of Law Reconstruction, 2020)
Waqf is a religious institution in Islam, and is included in the category of community worship which is a means and capital is essential to promote the development of religion. Evidence used as the basis sharia endowments text derives from an understanding of the Qur'an and Sunnah. Then understand and using law endowments not merely textual law or fiqh, but must dare to seek renewal of the school's endowment to be able to prosper the people, because the basic assumption of the law is an institution that aims leads man to live a fair, prosperous and make human happy. The type of research is socio-legal research is explorative, descriptive. With the approach of the law and the case approach, Source data: derived from the primary data, which is data obtained from field practice. The development of waqf law reform must begin with a deeper study of waqf as ijtihad region, as well as the legal principles of waqf is a truth that is used as the foundation of thinking and reason opinion, the reform ideology, law enforcement and implements a waqf.